Technology Shocks and Aggregate Fluctuations : How Well Does the RBC Model Fit Postwar U.S. Data? - Gali Garreta, Jordi (IMF Working Papers; Working Paper ;, 2004)
Our answer: Not so well. We reached that conclusion after reviewing recent research on the role of technology as a source of economic fluctuations. The bulk of the evidence suggests a limited role for aggregate technology shocks, pointing instead to demand factors as the main force behind the strong positive comovement between output and labor input measures.